2017
DOI: 10.1016/j.vaccine.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Cross-protection to new drifted influenza A(H3) viruses and prevalence of protective antibodies to seasonal influenza, during 2014 in Portugal

Abstract: Introduction: Immune profile for influenza viruses is highly changeable over time. Serological studies can assess the prevalence of influenza, estimate the risk of infection, highlight asymptomatic infection rate and can also provide data on vaccine coverage. The aims of the study were to evaluate pre-existing cross-protection against influenza A(H3) drift viruses and to assess influenza immunity in the Portuguese population. Materials and methods: We developed a cross-sectional study based on a convenience sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The pattern of influenza virus circulation varies or remains same throughout the year depending upon genetic re-assortment or seasonal influence. This may results in epidemic or pandemic that can alter the intervention action concerning vaccination program and other preventive measures of a country [11]. Previous records also show that pandemic in the past was either due to antigenic shift with strains from the avian reservoir or by direct introduction of an avian strain into the human population [6].…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of influenza virus circulation varies or remains same throughout the year depending upon genetic re-assortment or seasonal influence. This may results in epidemic or pandemic that can alter the intervention action concerning vaccination program and other preventive measures of a country [11]. Previous records also show that pandemic in the past was either due to antigenic shift with strains from the avian reservoir or by direct introduction of an avian strain into the human population [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite higher rates (64%-65%) of vaccination in both cohorts going into the second season, controls had a greater attack rate than cases in season 2, possibly due to natural immunity in cases, having had recent influenza. Cross protection against drifted A strains has been demonstrated, 20 and a previous study of back-to-back H3N2 epidemics showed some cross protection and very high levels of seroprevalence after each epidemic. 21 Having had influenza B may not have been as protective against the new strain as having had influenza A in season 1, although the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 75%
“…Identi cation of in uenza virus infection by rapid tests can facilitate prompt implementation of control measures before con rmatory test results are available from shell vial culture, tissue cell viral culture, or RT-PCR. In particular, a wide range of sensitivities of the rapid in uenza tests have been reported, where as speci cities have been reported to be high, compared with reference tests [1,[8][9][10][11][12]. In the context of enrolling participants in studies to knowledge of transmission of in uenza virus,a rapid in uenza diagnostic test was used to screen persons with in uenza-like illness in the Nepal during the 2016 in uenza seasons.…”
Section: Introductionmentioning
confidence: 99%